“Determinación de los niveles de estrés en pacientes previa a la consulta odontológica en el Hospital provincial General Docente de Riobamba.” - Balarezo Mora, Narcisa Alexandra (2017)
The title of this research project is "Determination of stress levels in patients prior to dental consultation at the Hospital Provincial General Docente de Riobamba". It is evidenced that "Psychology and Dentistry are non-exclusive science and maintain several common points and interests." The purpose is to assess the predominant stress levels in patients that attend prior dental appointment since it has been observed that many patients make treatment difficult. The objective is to determine the stress levels in patients prior to dental consultation, at the same time making proposals for the stress reduction. The applied methodology is a quantitative study, cross type, descriptive level and bibliographic research. The sample was non-probabilistic of an accidental or deliberate type of 145 patients; men 44 and women 101, evaluated using the Hamilton scale 3 test. The independent variable: stress, dependent variable: prior attention to dental consultation. The results and statistical analysis by the SPSS are: mild stress levels in the female gender of (61%), in the group from 20 to 39 years the mild stress level of (48.84%), in subsequent dental care a mild stress level of (77%) and in the dental specialty - primary health care the mild stress level of (62%). It is concluded that there are stress levels: mild and moderate, predominating the mild stress, which can make difficult to treat oral health.